A Study On Real Estate Investment Decisions in an Indonesian Free Trade Zone: A Behavioral Finance Approach - Cindy Lorenza; Dezie Leonarda Wargenegara (Universitas Medan Area, 2022)
The study use behavioral finance approach to explore the factors that influence investment decisions in real estate investing in FTZ Batam. Behavioral finance is a branch of finance that studies psychology and sociology to evaluate the investment decision-making process and investors' responses to market conditions. Overconfidence, risk aversion, herding bias, and financial literacy are independent variables that are thought to influence investment decisions in real estate at FTZ based on a behavioral finance perspective. This study was conducted on 185 respondents who were selected based on several considerations such as age, investment, income, etc. to obtain representative data and are residents of Batam. The data was processed using smartPLS (Partial Least Square) using the PLS-SEM (Partial Least Square-Structural Equation Modeling) method. In this study, overconfidence, imitation, and financial literacy showed a significant and positive effect. Meanwhile, risk aversion has no significant and positive effect on real estate investment decisions in Batam.